2014
DOI: 10.1177/0363546514536021
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Allograft Transplantation

Abstract: Meniscal allograft transplantation seems to provide good clinical results at short-term and midterm follow-up, with improvement in knee function as well as acceptable complication and failure rates. Higher quality studies are necessary to better assess the potential chondroprotective effect of MAT and to identify differences in terms of outcomes between different surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 99 publications
8
177
1
2
Order By: Relevance
“…Worse outcomes have been reported without these corrections. 19 The acceptable degree of chondral loss is controversial, but the presence of full thickness chondral loss results in a poor local mechanical environment for the meniscal transplant to survive. Traditionally, meniscal transplantation was contraindicated in the presence of chondral loss (Outerbidge IV or ICRS 3b or 3c), but recently surgeons have accepted a higher failure rate in such patients and have combined transplantation with articular cartilage repair techniques.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worse outcomes have been reported without these corrections. 19 The acceptable degree of chondral loss is controversial, but the presence of full thickness chondral loss results in a poor local mechanical environment for the meniscal transplant to survive. Traditionally, meniscal transplantation was contraindicated in the presence of chondral loss (Outerbidge IV or ICRS 3b or 3c), but recently surgeons have accepted a higher failure rate in such patients and have combined transplantation with articular cartilage repair techniques.…”
Section: Indicationsmentioning
confidence: 99%
“…20 Pooled complication rates for isolated meniscal transplantation have ranged from 6 to 11%, although this is likely to significantly underestimate the true complication rate, as followup in some studies did not appear to be comprehensive. 19,25 One recently published large study (200 patients) found a 32% reoperation rate following meniscal allograft transplantation, with the majority of cases being just a simple debridement. 26 The average graft survival time has been reported to be between 10 and 16 years.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…9 Complications often lead to additional surgical management. On the other hand, complication rates in MAT are low to acceptable 4,12,13 with reportedly low reoperation and revision rates even in an athletic population. 14 …”
Section: Introductionmentioning
confidence: 96%
“…These patients may be treated by meniscal allograft transplantation (i.e. replacement of the native tissue with a donor meniscus) to relieve pain and restore knee function (Rosso et al, 2014). However, problems related to the availability and sizing of allografts, the risk of disease transmission and post-implantation remodeling (Lee et al, 2012;Wada et al, 1998), have driven the search for an alternative treatment.…”
Section: Introductionmentioning
confidence: 99%